Comparison of adequacy of birth weight for gestational age according to different intrauterine growth curves - Tenório,Micaely Cristina dos Santos (2019)
Abstract Objectives: to compare the assessment of the adequacy of birth weight for gestational age according to different intrauterine growth curves. Methods: across-sectional study, which analyzed gestational and neonatal information from 344 mother-newborn binomials. Birth weight data were analyzed using the International Fetal and New Born Growth Consortium for the 21st Century (INTERGROWTH-21st) and compared with the growth curves proposed by Alexander et al. and Fenton & Kim. Newborns were classified as small for gestational age (SGA), suitablefor gestational age (SUGA) or large for gestational age (LGA). Results: among the newborns, 51.2% were male, and 93.0% were born at term. Higher prevalence of SUGA and LGA and lower SGA was found by the INTERGROWTH-21st curves when compared to the references of Fenton & Kim and Alexander et al. Moderate agreement was observed in detecting birth weight by different growth curves. Conclusions: there was a lower detection of SGA infants and a higher screening, especially of LGA infants, in the INTERGROWTH-21st evaluation, when compared to the growth curves of Fenton & Kim and Alexander et al.